1989
DOI: 10.1103/physrevb.40.3197
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation of alloy phase diagrams: The renormalized-interaction approach

Abstract: We present a formalism for calculating the temperature-composition phase diagrams of isostructural solid alloys from a microscopic theory of electronic interactions. First, the internal energy of the alloy is expanded in a series of volume-dependent multiatom interaction energies. These are determined from self-consistent total-energy calculations on periodic compounds described within the local-density formalism. Second, distant-neighbor interactions are renormalized into composition-and volume-dependent effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
112
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(123 citation statements)
references
References 121 publications
5
112
0
1
Order By: Relevance
“…This theoretical prediction of very high critical temperature indicated very limited solid solution in (BN) x (C 2 ) 1-x alloys, which can't well interpret Badzian's report 1 of the synthesis of solid solutions within the compositional range 0.15<x BN <0.6. Two possible explanations could account for this discrepancy: (i) Mixing in the experiments took place in the liquid state and the solid solutions are metastable systems, as pointed out by Lambrecht et al 4 ; (ii) additional short-range ordered structures should be included to form a representative basis for all zinc blende structures to account for possible short-range interactions, as shown by Ferreira et al 20 . Specifically, the (111) orientation should be included, which we have shown to be the lowest-energy possible structure (Fig.…”
mentioning
confidence: 99%
“…This theoretical prediction of very high critical temperature indicated very limited solid solution in (BN) x (C 2 ) 1-x alloys, which can't well interpret Badzian's report 1 of the synthesis of solid solutions within the compositional range 0.15<x BN <0.6. Two possible explanations could account for this discrepancy: (i) Mixing in the experiments took place in the liquid state and the solid solutions are metastable systems, as pointed out by Lambrecht et al 4 ; (ii) additional short-range ordered structures should be included to form a representative basis for all zinc blende structures to account for possible short-range interactions, as shown by Ferreira et al 20 . Specifically, the (111) orientation should be included, which we have shown to be the lowest-energy possible structure (Fig.…”
mentioning
confidence: 99%
“…Previous studies on several alloy systems [3,4,12] have shown that, for the fcc lattice, incorporation of pair interactions up to the 4NN is sometimes essential to obtain the correct ground states. To include interactions with this spatial extent, we have formulated the fcc ground state problem with the 13 and 14 point cluster as maximal clusters.…”
Section: Formausmmentioning
confidence: 99%
“…The first principles approaches for calculating ECl's fall into three main classes: 1) Methods based on a perturbative treatment of the coherent potential approximation (CPA), most notably, the generalized perturbation method (GPM) [11], 2) Methods involving the calculation of energies of ordered superstructures, and, in conjunction with expansion (1), extraction of the ECl's from these computations [4,5], and 3) The method of direct configurational averaging (DCA) [6]. DCAis a method of perturbing not the averaged, CPAmedium, but rather a truly randomly generated configuration.…”
Section: Formausmmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to alloys, where the unit cell is composed of the exchangeable atoms solely, minerals often contain extra "inactive" elements, e.g., O, Si, Al, and C, which increase the system size. Typically one is concerned with ordering and mixing of cations of different metals which rest within an "inert" matrix built by anion complexes such as SiO 4 4− , AlO 6 9− , or CO 3 2− . The low symmetry and the chemical complexity typically imply a large unit cell, where the mixing occurs within a specific sublattice ͑Wyckoff position͒.…”
Section: Introductionmentioning
confidence: 99%